A DETERMINAN PERILAKU KEWIRAUSAHAAN DAN KINERJA BISNIS PETANI LADA - Rufti Puji Astuti; Novyandra Ilham Bahtera (Journal of Integrated Agribusiness, 2022)
In the last few years, the business performance of muntok white pepper has gradually decreased. The reducing production of pepper, the declining area of pepper plantation, and the decreasing income of pepper farmer are the phenomenon that pepper’s business performance is weak. The study aims to analyse the determinants of entrepreneurial behaviour and its business performance as well as to determine the dominant factors between internal and external factors. The survey was used as the research method with purposive sampling as the sampling method. 90 farmers involved as the respondents of the study. Structural equation modelling with smart partial least squares was applied to analyse the data. The study found that the entrepreneurial behaviour of pepper farmer was positively significant in affecting the business performance. The changing of pepper income was the most powerful indicator in reflecting the business performance. The entrepreneurial characteristics and the personal factors as the internal factor as well as environmental factor as the external factor influenced both entrepreneurial behaviour and business performance. The ethnicity as the internal factor played a vital role in affecting the entrepreneurial behaviour and business performance. Through entrepreneurial characteristics as the internal factor, the direct effect of entrepreneurial behaviour towards business performance was bigger than the indirect effect of both internal and external factors towards the business performance. It indicated that the internal and external supports were inadequate to improve the business performance if the pepper farmer had no entrepreneurial behaviour in managing farming activities.